Exergy Performance Investigation of Eco-Friendly Refrigerant Mixtures as an Alternative to R134a in a Domestic Refrigerator. (8th February 2022) - Baskaran, A.; Manikandan, N.; Tesfaye, Jule Leta; Nagaprasad, N.; Krishnaraj, Ramaswamy
Abstract : In this paper, various eco-friendly refrigerant mixtures R430A, R436A, R436B, R435A, and R510A used in vapour compression refrigeration systems are considered for this study. All of them have zero ODP and very low GWP. On the basis of exergy features, the efficiency of various working fluids in vapour compression refrigeration cycles was compared. The exergy efficiency of mixtures is evaluated for various evaporating temperatures ranging from -40°C to -5°C at a constant condensation temperature of 45°C. The variation of exergy is also analyzed for various condensation temperatures ranging from 25°C to 60°C at a constant evaporating temperature of -10°C. The exergy losses in various components are computed and presented in Grassmann diagrams for a cooling load of 1 kW. The results indicate that all the investigated alternative refrigerant mixtures have higher exergy efficiency than R134A. The maximum exergy performance is 39.72% observed for the mixture R435A at an evaporation temperature of -30°C, and this value is 9.89% higher than that of R134a.The results also show that the highest and lowest exergy losses have occurred in the compressor and evaporator.